1994
DOI: 10.1080/00087114.1994.10797299
|View full text |Cite
|
Sign up to set email alerts
|

Penetration and early colonization in basidiospore-derived infection ofMelampsora pulcherrima(Bub.) Maire onMercurialis annuaL.

Abstract: SUMMARY -The early phases of basidiospore-derived infection of Me/ampsora pulcherrima (Bub.) Maire on the leaves of Mercurialis annua L. were studied by light microscopy, SEM and TEM. The fine morphology of the basidiospore germling penetration and intraepidermal infection structures is discussed in comparison with that of other rusts recently described. The direct penetration through the epidermal cell wall, characteristic of the rust basidiospore-derived germlings, is confirmed. The absence of an extrahyphal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
(38 reference statements)
0
12
0
1
Order By: Relevance
“…Consequently, in order to fit themselves onto a substratum with the above characteristics, it would be necessary for the basidiospore germlings to modify their way of penetration from the direct one, which is typical of the rust monokaryotic phase, to that of the indirect type. Notwithstanding, Longo et al (2000) observed that the morpho-functional characteristics of the penetration structures of C.flaccidum remained those of a monokaryotic phase, even if this indirect penetration recalled the mode of penetration (through the stomatal aperture) of a dikaryon.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Consequently, in order to fit themselves onto a substratum with the above characteristics, it would be necessary for the basidiospore germlings to modify their way of penetration from the direct one, which is typical of the rust monokaryotic phase, to that of the indirect type. Notwithstanding, Longo et al (2000) observed that the morpho-functional characteristics of the penetration structures of C.flaccidum remained those of a monokaryotic phase, even if this indirect penetration recalled the mode of penetration (through the stomatal aperture) of a dikaryon.…”
Section: Introductionmentioning
confidence: 91%
“…One other case of indirect basidiospore-derived penetration on gymnosperms was proposed by Ragazzi et al (1987) and Ragazzi and Dellavalle Fedi (1992) Longo et al (2000) demonstrated that the basidiospore-derived penetration of C. flaccidum on Pinus pinea was effectively indirect through the stomata, giving rise to a substomatal infection structure on all types of host needles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, subsequent studies on the penetration of the basidiospore germ tubes of sev eral rust fungi on their hosts (MILLER et al 1980;GRAY et al 1983;GOLD andMENDGEN 1984, 1991;HOPKIN et al 1988; LONGO et al 1988LONGO et al , 1991LONGO et al , 1994LONGO et al , 1997MORIN et al 1992) confirmed direct penetration for these spores and consid ered the indirect penetration of (i) C.ribicola on P.strobus (PATTON and JOHNSON 1970) and (ii) Cronartium comandrae Pk. on Pinus banksiana Lamb.…”
Section: Introductionmentioning
confidence: 99%